RIPK3 and AXL Expression Study in Primary Cutaneous Melanoma Unmasks AXL as Predictor of Sentinel Node Metastasis: A Pilot Study - Nicolè, Lorenzo; Cappello, Filippo; Cappellesso, Rocco; Piccin, Luisa; Ventura, Laura; Guzzardo, Vincenza; Del Fiore, Paolo; Chiarion-Sileni, Vanna; Dei Tos, Angelo Paolo; Mocellin, Simone; Fassina, Ambrogio (Frontiers in Oncology, 2021)
Malignant Melanoma (MM) is the most lethal skin cancer. AXL is a tyrosine kinase receptor involved in several oncogenic processes and might play a role in blocking necroptosis (a regulated cell death mechanism) in MM through the downregulation of the necroptotic-related driver RIPK3. The aim of this study was to evaluate the clinical impact of the expression of AXL and RIPK3 in 108 primary cutaneous MMs. Association between AXL and RIPK3 immunoreactivity and clinic-pathological variables, sentinel lymph node status and tumor infiltrating lymphocytes (TILs), was assessed. Immunoreaction in tumor cells was detected in 30 cases (28%; range 5%-80%) and in 17 cases (16%; range 5%-50%) for AXL and RIPK3, respectively. Metastases in the sentinel lymph nodes were detected in 14 out of 61 patients and these were associated with AXL-positive immunoreactivity in the primary tumor (p < 0.0001). No association between AXL and TILs was found. RIPK3 immunoreactivity was not associated with any variables. A final logistic regression analysis showed Breslow and AXL-positive immunoreactivity as the stronger predictor for positive sentinel node status (AUC of 0.96). AXL could be a potential new biomarker for MM risk assessment, and it deserves to be further investigated in larger studies.